2017
DOI: 10.1111/anu.12503
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic krill (Euphausia superba ) meal in the diets improved the reproductive performance of tongue sole (Cynoglossus semilaevis ) broodstock

Abstract: A three-month feeding trial was conducted to investigate the effects of dietary krill meal on the reproductive performance of tongue sole broodstock. Three diets were formulated to contain different levels of krill meal, 0 (Diet K-0), 10 (K-100) and 200 (K-200) g kg -1 dry matter, replacing the corresponding contents of protein and lipid from fishmeal and fish oil. Each diet was assigned to triplicate tanks. Compared with K-0, both K-100 and K-200 increased the egg properties such as buoyant eggs rate, egg dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The demand for high-quality protein sources in the rapidly expanding aquaculture sector is growing, as the supply of highly preferable fishmeal (FM) is decreasing, while its price is increasing daily. Meals containing soybeans, cottonseed, rapeseed, corn, lupins, canola, barley, potato, insects, krill, squid and by-products have been used during the last couple of decades for different species (Alam et al, 2012;Barroso et al, 2014;Belghit et al, 2018Belghit et al, , 2019Biswas et al, 2007Biswas et al, , 2017Biswas et al, , 2019Bu et al, 2017;Cheng et al, 2010;Cruz-Suárez et al, 2007;Dossou et al, 2018;Faudzi et al, 2018;Gatlin et al, 2007;Henry et al, 2015;Kader et al, 2010Kader et al, , 2012Kissil et al, 2000;Lock et al, 2015;Salze et al, 2010;Sánchez-Muros et al, 2014;Silva-Carrillo et al, 2012;Takakuwa et al, 2020;Xu et al, 2017;Zhang et al, 2014). However, concerns over the future availability of some of these ingredients together with the existence of anti-nutritional factors, inferior quality and quantity of nutrient content suggest that alternative protein sources need to be continuously explored.…”
Section: Introductionmentioning
confidence: 99%
“…The demand for high-quality protein sources in the rapidly expanding aquaculture sector is growing, as the supply of highly preferable fishmeal (FM) is decreasing, while its price is increasing daily. Meals containing soybeans, cottonseed, rapeseed, corn, lupins, canola, barley, potato, insects, krill, squid and by-products have been used during the last couple of decades for different species (Alam et al, 2012;Barroso et al, 2014;Belghit et al, 2018Belghit et al, , 2019Biswas et al, 2007Biswas et al, , 2017Biswas et al, , 2019Bu et al, 2017;Cheng et al, 2010;Cruz-Suárez et al, 2007;Dossou et al, 2018;Faudzi et al, 2018;Gatlin et al, 2007;Henry et al, 2015;Kader et al, 2010Kader et al, , 2012Kissil et al, 2000;Lock et al, 2015;Salze et al, 2010;Sánchez-Muros et al, 2014;Silva-Carrillo et al, 2012;Takakuwa et al, 2020;Xu et al, 2017;Zhang et al, 2014). However, concerns over the future availability of some of these ingredients together with the existence of anti-nutritional factors, inferior quality and quantity of nutrient content suggest that alternative protein sources need to be continuously explored.…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe et al (1991) and Saleh et al (2013) observed improved egg quality and larval growth in red seabream after feeding diets containing frozen raw KM and krill phospholipids respectively. Antarctic KM inclusion up to 10% into the diets of tongue sole (Cynoglossus semilaevis) significantly increased the reproductive performance of fish (Xu et al, 2017). However, in many cases, total FM replacement by krill products or inclusion of high levels of KM tended to suppress the performance of fish (Olsen et al, 2006;Ringø et al, 2006;Suontama, Karlsen, et al, 2007;Yoshitomi, Aoki, & Oshima, 2007).…”
mentioning
confidence: 99%
“…The n-3 series and n-6 series fatty acids account for 45.41% and 2.24%, respectively [ 41 ]. Dietary supplementation with Antarctic krill meal increased the content of EPA and n-3 PUFA while decreasing n-6 PUFA content in tongue sole embryos [ 42 ]. The composition of egg fatty acids is positively correlated with the composition of fatty acids in the diet.…”
Section: Discussionmentioning
confidence: 99%